“ALL TRUTH IS RELATIVE” OR HOW TO NOT BE FOOLED IN THE POST-TRUTH AGE? - Sargsyan, Mariana (Armenian Folia Anglistika, 2023)
The term “fake news” is not a new phenomenon. Before the advent of the Internet, people read news from reliable sources which were required to adhere to strict standards of professional ethics. However, due to the ease of access to the Internet and social media there have emerged new ways of publishing, sharing and consuming news and information, in the meanwhile, the control over the quality and editorial norms have declined significantly. This has changed the way fake news is created and distributed. People now prefer to read the information on social media and other online sources. However, it is not always easy to determine which content is true and which is not. The paper argues that fake news employs specific language and graphic patterns which are meant to generate an emotional response. Knowing the language features of fake news may help readers become less susceptible to fake content. The study is built on the hypothesis that a critical analysis of how the information is represented activates a process of reasoning that helps spot fake content.
Keywords: post-truth; fake news; language and graphic patterns; critical approach; emotion; cognitive aspect